General Characteristics of Practices and Non-Practices Farmers and Their Opinions on Good Agriculture Practice in Adana Province - Hilal Yılmaz; Cengiz Sağlam; Mevlüt Gül; Başak Aydın; Tugay Ayasan (Turkish Journal of Agriculture: Food Science and Technology)
The agricultural production model which is done in order to provide food security, sustainability, and traceability in the agriculture, protect the natural sources and perform agricultural production, harmless to the environment, human and animal health, is called as Good Agricultural Practices. This study covers agricultural enterprises engaged in good agricultural practices and non-engaged in good agricultural practices in Adana province. The aim of the research is to compare the general characteristics of farms and to determine their views on good agricultural practices. The main material of the study constituted the primary data obtained through the survey of the 170 enterprises engaged in good agricultural and the non-used citrus (lemon and mandarin) farming in Adana province. According to the survey, it was determined that a higher level of education in enterprises engaged in ITU. The majority of good agricultural producers are residents in cities and towns and have social security. About 84.71% of good agricultural producers practise ITU in order to benefit support. It was determined that 25.88% of no good agriculture practices found ITU unnecessary. The 67.06% of producers stated that the market situation of the ITU products is similar to conventional products.